Shaloka Gurū Aṅgada Sāhiba : saṭīka - Sāhiba Siṅgha, 1894- (SAMP early 20th-century Indian books project, 1948)
Criticial interpretation of hymns by Angada Dewa, Guru, 1504-1552, in Ādi-Granth, Sikh canon.